Improving evolutionary decision tree induction with multi‐interval discretization. (23rd November 2017) - Saremi, Mehrin; Yaghmaee, Farzin
Abstract: Decision trees are a widely used tool for pattern recognition and data mining. Over the last 4 decades, many algorithms have been developed for the induction of decision trees. Most of the classic algorithms use a greedy, divide‐and‐conquer search method to find an optimal tree, whereas recently evolutionary methods have been used to perform a global search in the space of possible trees. To the best of our knowledge, limited research has addressed the issue of multi‐interval decision trees. In this paper, we improve our previous work on multi‐interval trees and compare our previous and current work with a classic algorithm, ie, chi‐squared automatic interaction detection, and an evolutionary algorithm, ie, evtree. The results show that the proposed method improves on our previous method both in accuracy and in speed. It also outperforms chi‐squared automatic interaction detection and performs comparably to evtree. The trees generated by our method have more nodes but are shallower than those produced by evtree.